Community programme captures hearts at Kampung Nyentil - Mohd Norfarhan, Mohd Mustafa
The two-hour boat ride, from the jetty of Kuala Medang in Kuala Lipis, will certainly be a lifelong treasured experience for 35 Universiti Malaysia Pahang (UMP) undergraduates, including five international students from Bangladesh, Indonesia and Pakistan.